A modern Sr/Ca‐δ18O‐sea surface temperature calibration for Isopora corals on the Great Barrier Reef. (24th February 2017) - Brenner, Logan D.; Linsley, Braddock K.; Potts, Donald C.
Abstract: Isopora (Acroporidae) is a genus of often encrusting, branching to submassive corals that are common in many shallow habitats on modern and fossil Indo‐West Pacific reefs. Although abundant, Isopora is largely absent from paleoceanographic literature. The scarcity of large Porites and the abundance of Isopora retrieved from the Great Barrier Reef (GBR) on Integrated Ocean Drilling Program Expedition 325 focused paleoceanographic attention on Isopora . Here we provide the first independent high‐resolution calibration of both Sr/Ca and δ 18 O for temperature analyses based on Isopora and demonstrate its consistency with Porites records. We developed modern skeletal Sr/Ca‐ and δ 18 O‐sea surface temperature (SST) calibrations based on five modern Isopora colonies from Heron Island in the southern GBR. Pairing the coral Sr/Ca record with monthly SST data yielded Sr/Ca‐SST sensitivities from −0.061 ± 0.004 (centered) to −0.083 ± 0.007 (raw) mmol/mol °C −1 based on reduced major axis regressions. These sensitivities are in the middle of the range of published Porites values and overlap most published values for Isopora, −0.075 ± 0.011 to −0.065 ± 0.011 mmol/mol °C −1 . The δ 18 O‐SST sensitivities range from −0.184 ± 0.014 (centered) to −0.185 ± 0.014 (raw) ‰ °C −1, assuming that all seasonal variation in δ 18 O was due to SST. These δ 18 O‐SST sensitivities are smaller than the widely accepted value of −0.23‰ °C −1 for biogenic aragonite but are at the upper end of high‐resolution Porites ‐defined sensitivities that are consistently less than the aforementioned established value. Our results validate the use of Isopora as an alternative source of paleoceanographic records in habitats where large massive Porites are scarce or absent. Key Points: Isopora temperature sensitivities are similar to accepted values for more commonly used corals Modern high‐resolution Isopora calibrations are well suited to reconstruct sea surface temperature Isopora are suitable for coral‐based paleoclimate reconstructions